Potensi Photodynamic Therapy (PDT) Berbasis Inhalable Curcumin sebagai Modalitas Terapi COVID-19 - Prasetyo, Aizar Vesa; Wulandari, Putri Ayu; Wahyuni, Putu Sinta Elix (Essence of Scientific Medical Journal; Vol 20 No 2 (2022): Volume 20 No. 2 (Juli - Desember 2022) Essential: Essence of Scientific Medical Journal, 2023)
Introduction: COVID-19 has become a new health crisis that threatens the world. Preventive efforts such as education and vaccination have been carried out. The only option available is the use of broad-spectrum antiviral drugs, but some of them tend to be expensive and have dangerous side effects. Curcumin has potential therapeutic effects for COVID-19 because of its antiviral and anti-inflammatory effects. Curcumin can be packaged in an inhalable form by formulating it into a dry powder. Applications using photodynamic therapy (PDT) can minimize systemic toxicity and unwanted side effects. Discussion: Curcumin has been shown to inhibit viral replication by inhibiting glycoprotein S and ACE 2, inhibiting the action of TMPRSS2, Main protease (Mpro), and decreasing the expression of the vacuolar pump (ATPase). Curcumin also can decrease the inflammatory response by inhibiting STAT3-mediated activation of NF-kB translocation. The formulation of curcumin inhalation therapy as a dry powder product can increase curcumin bioavailability and patient compliance. Curcumin-PDT on Vero cells infected with SARS-CoV2 exerted an anti-COVID-19 effect in vitro without causing cytotoxicity and apoptosis in cells, and had no adverse effect on plasma quality. Conclusion: Photodynamic therapy based inhalable curcumin has potential as a therapeutic innovation for COVID-19.